Two-year Outcomes after Transurethral Prostate Resection Post-prostatic Artery Embolization Versus Transurethral Prostate Resection Alone For Giant Benign Prostatic Hyperplasia - Zhiyu , Zhang; Zhen, Song; Qi, Zhou; Yuhua, Huang; Jun, Ouyang; Xuefeng, Zhang (Urology Journal, 2023)
Purpose: To compare the long-term (two-year) efficacy between transurethral resection of the prostate (TURP) after prostatic artery embolization (PAE) and TURP only for patients with giant (>100 mL) benign prostatic hyperplasia. Materials and Methods: We retrospectively analyzed data from 61 and 150 patients with giant benign prostatic hyperplasia treated with PAE+TURP or TURP alone, respectively, from January 2015 to March 2020. We compared index changes before and after surgery. Results: The operative time, intraoperative blood loss, postoperative bladder irrigation time, and catheter retention time in the PAE+TURP group were lower than those of the TURP group, while the speed of resection of the lesion and hospitalization costs were more significant (P < 0.05). International prostate symptom score (IPSS), quality of life (QoL), prostate volume, maximum urinary flow rate, detrusor pressure of maximum urinary flow rate, prostate-specific antigen, and urodynamic obstruction were better in the PAE+TURP group than the TURP group at 24 months (P < 0.05). Regarding IPSS and QoL scores at 24 months postoperatively compared with the preoperative period, the PAE+TURP group was better than the TURP group in terms of the storage period, voiding period, and QoL (P < 0.05). The distribution of postoperative adverse event severity classes was comparable between the groups (P = 0.984). Conclusion: In contrast to TURP alone, PAE + TURP is more expensive but provides better postoperative outcomes; there is no significant difference in terms of the severity grade distribution of postoperative complications.